Perkembangan Penyiapan Kepemimpinan Sekolah di Indonesia - Sumintono, B. (2017)
The dynamics of school leadership ideas and practice in Indonesia changes through times. It is reflecting the spirit of each era and adoption of leadership theory/practices that available. Government system and socio-political situation influence to education sector and impact to how principals leading and managing schools in Indonesia. As the new independence country in 1945, the Colonial influence with different purpose of schooling give foundation distinctively into Indonesia’s education. Significant development happened in 1970s when the New Order government expands the size of education sector, but little impact toward school leadership. The changing government system to decentralization in 2000s led to a drastic change about principalship in Indonesia. This new trend introduces principal standard requirement, systematic training and appointment by district government.